Agrowisata belimbing Karangsari, potensi lokal Kota Blitar sebagai sumber belajar biologi untuk meningkatkan literasi sains peserta didik - Shafila Sahnaz; Paramita Cahyaningrum Kuswandi (Jurnal Penelitian Pendidikan IPA, 2023)
The utilization of local potential as a biology learning source is still not maximized. This research focuses on integrating the local potential of Blitar, namely Karangsari’s Starfruit Agrotourism which was developed into a student worksheet app to increase students' science literacy. Karangsari’s Starfruit Agrotourism can be used as a learning resource on biodiversity material by discussing the diversity of starfruit (Averrhoa carambola) varieties, the use of starfruit, and efforts to preserve starfruit. Utilizing local potential and implementing the Sustainable Development Goals (SDG) in biology learning aligns with the Merdeka Belajar curriculum. This study used the ADDIE model which consists of analysis, design, development, implementation, and evaluation stages. The final product of this development research is a student worksheet app implemented to enhance science literacy in class X of students at SMAN 1 Blitar. Data was collected with needs questionnaires, teacher interviews, assessment questionnaires for material experts, media experts, biology teachers, student response questionnaires, and science literacy skills tests. The data obtained were statistically analyzed tests between subjects. Research results concluded as Karangsari’s starfruit agrotourism applied as the materials of the student worksheet app was declared feasible by experts, there are differences in science literacy between students who had taken part in learning while using the worksheet and students who did not, and the effect/contribution given by student worksheet apps to science literacy is 58%.